Das Offene Museum = The open museum : The first ten years = Die ersten zehn Jahre. - Broeker, Holger; Exhibition. Happy Birthday. Kunstmuseum Wolfsburg. 2004-05-29. 2004-08-15; Hahn, Carl H.; Köhler, Thomas; von Lüneburg, Susanne; Lütgens, Annelie; Meyric Hughes, Henry; Peyton-Jones, Julia; Rauch, Neo; Schnellecke, Ilona; Stoeber, Michael; van Tuyl, Gijs (Wolfsburg : Kunstmuseum Wolfsburg, 2004)
Leger, Fernand ; Welling, James ; Bustamante, Jean-Marc ; Man Ray ; Koons, Jeff ; Gilbert & George ; van der Leck, Bart ; Hujar, Peter ; Pistoletto, Michelangelo ; Colla, Ettore ; Seta, Enrico ; Branzi, Piergiorgio ; Bevilaqua, Carlo ; Brouwn, Stanley ; Graham, Paul ; Herold, Georg ; Araki, Nobuyoshi ; Paik, Nam June ; Andre, Carl ; Immendorff, Jörg ; Wall, Jeff ; Tillmans, Wolfgang ; Akerman, Chantal ; Chamberlain, John ; Bulloch, Angela ; Starr, Georgina ; Lucas, Sarah ; Chapman, Dinos & Jake ; Borland, Christine ; Goldin, Nan ; Nauman, Bruce ; Merz, Mario ; Donzelli, Pietro ; Kupka, Frantisek ; Rhoades, Jason ; Kienholz, Edward ; Hockney, David ; Ruscha, Ed ; Burden, Chris ; McCarthy, Paul ; Therrien, Robert ; Kiefer, Anselm ; Fischli, Peter ; Weiss, David ; Gursky, Andreas ; Peyton, Elizabeth ; Daniels, René ; Warhol, Andy ; Mori, Mariko ; Storey, Helen ; Miyake, Issey ; Man Ray ; Duchamp, Marcel ; Miro, Joan ; Masson, Andre ; Kounellis, Jannis ; Schütte, Thomas ; Sherman, Cindy ; McCollum, Allan ; Tuymans, Luc ; Hoderlein, Stefan ; Friedl, Peter ; Exler, Stefan ; Majerus, Michel ; Pommerer, Peter ; Meese, Jonathan ; Schütte, Thomas ; van der Elsken, Ed ; Tinguely, Jean ; Lockhart, Sharon ; Lichtenstein, Roy ; Hume, Gary ; Peyton, Elizabeth ; Weiner, Lawrence ; Aitken, Doug ; Hanson, Duane ; Hirst, Damien ; McCarthy, Paul ; Hadid, Zaha ; Avedon, Richard ; Hill, Gary ; Ruscha, Ed ; Prince, Richard ; Butler, Reg ; Chadwick, Lynn ; Moore, Henry ; Caulfield, Patrick ; Cragg, Tony (Anthony) ; Hamilton, Richard ; Caro, Anthony ; King, Phillip ; Huxley, Paul ; Flanagan, Barry ; Long, Richard ; Gormley, Antony ; Kapoor, Anish ; Oehlen, Albert ; Murakami, Takashi ; Parker, Erik ; Ritchie, Matthew ; Ruyter, Lisa ; Patterson, Richard ; Essenhigh, Inka ; etc.
boek
Keywords: Wolfsburg